G221(P) A service evaluation of neonatal presentations to the paediatric emergency department. (27th April 2016) - Kirkwood-Wilson, R; Huang, S; Jenner, R
Abstract : Aims: There are a lack of clear clinical pathways guiding emergency clinicians in the investigation and management of neonates presenting to the Paediatric Emergency Department (PED). Anecdotally, there are high levels of anxiety amongst junior staff about discharging this patient group without a period of observation, normal investigation results or before receiving advice from a paediatrician. The aims of this study were to determine the profile of neonatal visits to the PED and identify which clinical pathways would be useful when managing this patient group. In turn, we aimed to develop evidence-based guidelines for use within the PED and establish when a stream-lined referral to paediatrics would be indicated. Methods: We retrospectively reviewed the case notes of 480 infants, less than 28 days old, presenting to the PED from January to December 2014. Re-attenders were excluded. Source of referral, presenting complaint, investigations, final diagnoses, referral to paediatrics and admission rate were analysed. The significance of prematurity and perinatal problems was also examined. Results: From the 480 neonates analysed, 56% were male. The most common presenting complaints were jaundice (15%), increased work of breathing (9%), weight loss (9%) and vomiting (9%). The most frequent diagnoses were normal baby (36%), jaundice requiring treatment (11%), bronchiolitis (8%) and poor establishment of feeding (7%). Investigations were performed in 58% of neonates and 67% were referred to paediatrics. The overall admission rate was 58%. 28% of neonates were referred by midwives; 73% of these were admitted. Prematurity and a history of perinatal problems increased admission rate to 77% and 79%, respectively. Conclusion: There is a relationship between non-acute neonatal visits to the PED and insufficient caretaker knowledge or high levels of parental anxiety. More detailed education and early postnatal support may help to decrease non-acute visits by neonates. Appropriate training of PED staff and utilisation of clinical care pathways pertaining to the management of common neonatal presentations, will avoid unnecessary tests and admissions, without overlooking signs of serious illness. A stream-lined referral to paediatrics may be indicated in neonates referred by midwifes and those with a history of prematurity and/or perinatal problems.